IMPLEMENTASI MODEL ATIK UNTUK MENINGKATKAN LITERASI NUMERASI PADA ANAK USIA 5-6 TAHUN DI TK MAMBAUL ULUM - Siti Istiadah; Gunawan; Ahmad Afandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Through the use of the ATIK Observe, Imitate, and Do Model, this study seeks to improve children's numeracy literacy, especially in understanding the symbols of numbers 1–10. Based on the results of observations, students' numeracy literacy in understanding the symbols of numbers 1–10 is still low, namely sometimes they are still wrong in writing or calculating numbers, such as writing them backwards, making it difficult to distinguish one number symbol from another.